2018
DOI: 10.1038/s41598-018-33699-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental filtering effect on the daylight operation of a free-space quantum key distribution

Abstract: One of the challenges of implementing free-space quantum key distribution (QKD) systems working in daylight is to remove unwanted background noise photons from sunlight. Elaborate elimination of background photons in the spectral, temporal, and spatial domains is an indispensable requirement to decrease the quantum bit error rate (QBER), which guarantees the security of the systems. However, quantitative effects of different filtering techniques and performance optimization in terms of the secure key rate have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…This source of background photons is perhaps the most difficult obstacle to continuous global coverage. Timing information, as well as information about the spectral and spatial profile of the signal, can help reduce the noise via filtering, but only to a certain extent (see, for e.g., refs 70,99 ). Furthermore, because the probability to transmit single photons from satellite to ground is quite low, the communicating parties must ensure that the probability to collect background photons is even lower in order to ensure a high signal-to-noise ratio (SNR), and thus a high fidelity for the received quantum state.…”
Section: Overview Of Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This source of background photons is perhaps the most difficult obstacle to continuous global coverage. Timing information, as well as information about the spectral and spatial profile of the signal, can help reduce the noise via filtering, but only to a certain extent (see, for e.g., refs 70,99 ). Furthermore, because the probability to transmit single photons from satellite to ground is quite low, the communicating parties must ensure that the probability to collect background photons is even lower in order to ensure a high signal-to-noise ratio (SNR), and thus a high fidelity for the received quantum state.…”
Section: Overview Of Simulationsmentioning
confidence: 99%
“…(34). In order to calculate R, we let λ = 810 nm, Δλ = 1 nm, Ω fov = 100 μsr, r = 0.5 m, and ΔT = 1 ns; see, for e.g., refs 70,99,110 . from the context.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Furthermore, our finding suggests that payloads optimised for operation with high background levels of light may be beneficial to extend coverage at high latitudes during the summer months, e.g., 1550-nm operation and aggressive temporal, spatial and spectral filtering. A shift toward 1550 nm would be also desirable in order to implement intersatellite links [42][43][44][45]. This may however compromise peak key distribution rates; hence, further studies will be needed to perform optimisation across payload and mission parameters coupled with a detailed key-demand and network-usage model including key buffering and refresh rates.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, some nonzero key rates may be possible with small levels of background light and a more detailed simulation incorporating site-level background light and astronomical data, e.g., position of the moon, is in development. SatQKD systems that can operate in daytime are currently under development by various groups [42][43][44][45] but not yet fully demonstrated in orbit. On the other hand, when the constellation is required to distribute keys not only to a single gateway but also to all gateways, the best case scenario secret key volume decreases to 160 kbit/night/satellite, which is also in southeast England.…”
Section: Introductionmentioning
confidence: 99%
“…However, the first downlink microsatellite QKD experiment was just realized very recently in 2017 with a QBER less than 3% and 99.4±4.4% degree polarization by Takenaka et al [38]. Several authors investigated the protocol using single photons and demonstrated the feasibility of free-space satellite-to-ground QKD with significant improvements regarding the QBER, the communication distance and the sifted key rate in the night-time as well as under noisy-like sunlight daytime [26,29,[39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%